2018
DOI: 10.1016/j.jacbts.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Vagal Nerve Stimulation Ameliorates Pulmonary Vascular Remodeling and Improves Survival in Rats With Severe Pulmonary Arterial Hypertension

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 37 publications
7
59
0
Order By: Relevance
“…This is of particular importance when VNS is delivered therapeutically, wherein standardized doses are desirable within and in between animals, and across time. Previous reports from rat and large animal models implemented a similar approach to adjust stimulation intensity using respiratory twitching [15,71], and heart rate [40,72,73] to standardize stimulation protocols, but not on a dose-by-dose basis. Notably, electrical impedance, which is commonly used as a measure of electrode integrity and performance [74], did not correlate well with changes in HRT on an individual implant basis as implants aged (Fig 3E).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is of particular importance when VNS is delivered therapeutically, wherein standardized doses are desirable within and in between animals, and across time. Previous reports from rat and large animal models implemented a similar approach to adjust stimulation intensity using respiratory twitching [15,71], and heart rate [40,72,73] to standardize stimulation protocols, but not on a dose-by-dose basis. Notably, electrical impedance, which is commonly used as a measure of electrode integrity and performance [74], did not correlate well with changes in HRT on an individual implant basis as implants aged (Fig 3E).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its approved use in treatment-resistant epilepsy [1] and depression [2], vagus nerve stimulation (VNS) may provide new treatment options for a wide range of illnesses. Long-term VNS is currently being explored in the treatment of brain disorders, such as tinnitus [3,4], stroke [5,6], and Alzheimer's disease [7,8], as well as peripheral organ and systemic diseases, including heart failure [9], cardiac arrhythmias [10][11][12][13], pulmonary hypertension [14,15], rheumatoid arthritis [16], Crohn's disease [17], and lupus [18]. The relatively recent discovery that the VN modulates the inflammatory response [19][20][21][22] might broaden the range of future indications for VNS, as inflammation is implicated in many common chronic diseases, such as type 2 diabetes, obesity, and atherosclerosis [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, clinical relevance of ANS disturbances in pulmonary arterial hypertension (PAH) has attracted attention as a new therapeutic target irrespective of the existence of HF (7,8). PAH is a chronic pulmonary vascular disease characterized by increased pulmonary vascular resistance (PVR) leading to right ventricular (RV) failure with associated ANS disturbances (9).…”
Section: Ans In Pulmonary Hypertensionmentioning
confidence: 99%
“…In most recent preclinical study using a rat model with PAH by Yoshida et al, the authors reported that VNS restored autonomic balance, decreased mean PA pressure, attenuated pulmonary vascular remodeling, and preserved RV function and also that VNS improved the survival rate in both the prevention and treatment protocols (8). Furthermore, in this study, acute VNS did not change nitric oxide synthesis or pulmonary vascular mechanics, despite acute as well as chronic VNS exhibiting significant inflammatory suppression in rats with PAH.…”
Section: Potential Mechanism Of Padn In Pulmonary Hypertensionmentioning
confidence: 99%